Analysis of Swirling Flow on Cyclone Separator Using CFD to Reduce Particulate Matter of Diesel Engine - S. Nurcholik; L. Adnyani; D. Sa’adiyah; L. Rahmah; R. Revari (SPECTA Journal of Technology, 2018)
Particulate matter (PM) is one of the component in flue gas of diesel engine. As one of air pollution, PM needs more attention, because its existence irritates respiratory. The using of cyclone as additional part of diesel engine, can reduce PM concentration before released to surrounding. However, the shape of cyclone affects the percentage of PM due to turbulence and length of track. In this paper, the prediction of swirling flow in different type of cyclone separator will be conducted by using Computational Fluid Dynamics (CFD). The analysis will focus on particle movement inside the cyclone separator and its turbulence phenomenon. There are four types of cyclone separator which will be observed: Perry’s method, Stairmand’s method, and the modification of each methods. All of these cyclone separator will have the same velocity inlet, and will be simulated using RNG k- model as the turbulence modelling. The simulation shows that the Stairmand’s method has the best turbulence and can collect most of PM.